Do energy-efficient homes improve residents' health? Evidence from insurers' records - Vincent P. Roberdel; Ioulia V. Ossokina; Jos van Ommeren; Theo Arentze (Tinbergen Institute, 2025)
This paper provides quasi-experimental evidence of the health benefits of a largescale, nationwide programme of home energy-efficiency retrofits in the Netherlands, exploiting individual medicine use from insurers' records. We demonstrate that these home upgrades improve children's health, as evidenced by a 4% reduction in the use of respiratory medication. We also find suggestive health improvements for other vulnerable groups, such as the poor.
Keywords: I10; Q40; R20; 330; Health; Energy efficiency; Renovation; Children; Public housing